Oscillation quenching in Stuart-Landau oscillators via dissimilar repulsive coupling - Subhasanket Dutta; Omar Alamoudi; Yash Shashank Vakilna; Sandipan Pati; Sarika Jalan (Physical Review Research, 2023)
Quenching of oscillations, namely, amplitude and oscillations death, is an emerging phenomenon exhibited by many real-world complex systems. Here, we introduce a scheme that combines dissimilar couplings and repulsive feedback links for the interactions of Stuart-Landau oscillators and analytically derive the conditions required for the amplitude death. Importantly, this analysis is independent of the network size, presents a generalized approach to calculate the stability conditions for various different coupling schemes, and befits nonidentical oscillators as well. Last, we discuss the similarities of the quenching of oscillations phenomenon with the postictal generalized Electroencephalogram (EEG) suppression in convulsive seizures.